Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $P_1=(a,y_a),P_2=(b,y_b), y\in C^1 (a,b), y_a>0,y_b>0$

And the area integral: $\int^b_a y(x) \sqrt{1+y'(x)}dx$

From the Euler differential-equation we obtain:

$$y'=1/\alpha \sqrt{y^2-\alpha^2}, \quad \alpha\in \mathbb R_0$$

Now the Author Book (Hans Sagan,Introduction to the calculus of Variations) concludes "Separation of Variables and substitution of $y=\alpha \cosh(t)$ yield

$$\alpha t+\beta =x$$ and hence,

$$y=\alpha \left(\cosh\left(\frac{(x-\beta)}{\alpha}\right)\right)$$

I can't reproduce this results, maybe you can see where i do go wrong:

$$y'=1/\alpha \sqrt{y^2-\alpha^2}, \quad \alpha\in \mathbb R_0$$

I do separate the variables:

$$\int \frac{dy}{\sqrt{y^2-1}}=\int dx$$

$\Longleftrightarrow \operatorname{arccosh}(y/\alpha)+\beta=x$, $\beta\in \mathbb R$ now theres obviously an $\alpha$ missing

but lets just go on and substitute like he does:" $y=\alpha \cosh(t)$"

$$\Longleftrightarrow \mbox{arccosh}(\alpha \cosh(t/\alpha )\alpha)+\beta=\mbox{arccosh}(t)+\beta=x$$

$\Longleftrightarrow t=\cosh(x-\beta)$ Which is wrong.

Also shouldn't he calculate the solution with the help of the limits a,b of the integral? I guess he just uses $\alpha$ and $\beta$ , because thats more convient for him in this case.

share|cite|improve this question
up vote 2 down vote accepted

Tiny mistakes. First of all, separation of variables should read $$ \alpha \int \frac{dy}{\sqrt{y^2-\alpha^2}} = \int dx $$ Taking $y = \alpha \cosh (t)$, then $dy = \alpha \sinh (t) \, dt$ and the integral becomes $$ \alpha\int \frac{dy}{\sqrt{y^2-\alpha^2}} = \alpha \int dt = \alpha t + \beta = \alpha \,\mbox{arccosh} \big(\frac{y}{\alpha}\big) + \beta, $$ hence $$ \alpha\,\mbox{arccosh}\big(\frac{y}{\alpha}\big) + \beta = x \Longleftrightarrow \mbox{arccosh}\big(\frac{y}{\alpha}\big) = \frac{x-\beta}{\alpha} $$ Finally $$ y = \alpha \cosh\left(\frac{x-\beta}{\alpha}\right). $$

About the limits, I guess you are right. It might be more convenient to do it this way.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.